Acknowledge the merits and limitations of exercise quantification methods to better control the dose-response relationship - Desgorces, F.-D.; Gouelle, A.; Noirez, P. (International Journal of Sports Physiology and Performance, 2026)
Background: Achieving a consensus on methods for exercise quantification appears to be a challenging endeavor in sport science. Quantification of exercise enables the description of training in unit doses by coaches and scientists, facilitating subsequent analysis of responses to training.